Hubungan Antara Pemanfaatan Penggunaan Bantuan Operasional Sekolah Dengan Prestasi Belajar Siswa Di Min Pucangsimo Bandarkedungmulyo Jombang - Masnuatul Khoiriyah; Atim S; Muhtadi (FAI- Undar, 2018)
Education is something that everyone should follow. With adequate education a person will be able to answer global challenges in life. With this education, the dignity of a person will be raised, the lower the level of education of a person, the dignity in the environment is also low. However, if someone has a high education, the higher the dignity of that person will be. Problem Formulation: Is there a relationship between the use of School Operational Assistance (BOS) assistance and student achievement at MIN Pucangsimo Bandarkedungmulyo Jombang? Research Objectives To determine whether there is a relationship between the use of BOS assistance and student achievement at MIN Pucangsimo Bandarkedungmulyo Jombang. Research Benefits: 1. Theoretically Add knowledge or insight for researchers and provide excellent information to those who need it and can provide discourse about the importance of the use of operational assistance and learning achievement at MIN Pucangsimo Bandarkedungmulyo Jombang. 2. Practically: From this research, it is hoped that it can be used as information for all educational institutions at the same level and can be a contribution of thought for general readers, for principals, teachers in particular. While the population of this research is students of MIN Pucangsimo Bandarkedungmulyo Jombang as many as 358 students. The samples used in this study were 32 students of class VI-a MIN Pucangsimo Bandarkedungmulyo Jombang with random sampling technique. Research Variables: The independent variables in this study were: